Long-term Results of Angulated Versus Hyperangulated Neck in Endovascular Aneurysm Repair With Endurant Endoprosthesis. (February 2023) - Özdemir-van Brunschot, Denise M. D.; Torsello, Giovanni Battista; Bernardini, Giulia; Litterscheid, Sarah; Torsello, Giovanni Frederico; Beropoulis, Efthymios
Purpose: Patients with a hyperangulated (>60°) proximal aortic neck and at high risk of open surgery have been treated with endovascular aortic repair (EVAR). However, long-term outcomes are not well reported. The aim of this study is to compare the technical and clinical success of EVAR in angulated (45°-60°) and hyperangulated (>60°) proximal neck angulation. Materials and Methods: The data of all consecutive patients undergoing EVAR treated between November 2007 and February 2020 were collected. A retrospective analysis of this prospective database was performed. The primary measure outcome was technical and clinical success. In addition, we evaluated sack evolution, type IA endoleak, secondary procedures, aneurysm rupture, mortality, aneurysm-related mortality, and migration. Results: In all, 246 of 1353 EVAR patients presented with an angulation of the proximal neck >45°, 130 patients presented with an infrarenal angulation >60°, while 116 patients had an angulation between 45° and 60°. Patients with a hyperangulated infrarenal aortic neck were significantly more often women (8.6% vs 26.9%), older (73.9 vs 76.7 years), and had less often diabetes mellitus (20.7% vs 10.8%). Suprarenal neck angulation and reversed tapered neck were significantly more frequent in the hyperangulated group so that propensity scores were generated using these anatomical parameters to create a matched cohort group. No significant differences in technical (87.9% vs 94.8%) and clinical success (66.4% vs 69.8%) were observed. After a mean clinical follow-up of 58.9 months significantly more secondary procedures were performed in the hyperangulated group (23.3% vs 12.9% p=0.04); however, neck-related secondary procedures were comparable (1.7% vs 6.0%; p=0.09). Also, all-cause and aneurysm-related mortality, sack evolution, type IA endoleak, aneurysm rupture, and migration were comparable for both groups. Conclusion: Compared with less angulated proximal aortic neck, hyperangulated neck anatomy did not reduce the technical and clinical success of EVAR but increased the risk of secondary procedures. In patients who are not good candidates for open surgery, EVAR is a reasonable alternative.